Temporomandibular Joint Dysfunction in a cohort of women with Rheumatoid Arthritis - Catarina Ambrósio; Renata Aguiar; Catarina Ambrósio; Inês Cunha; Anabela Barcelos (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2018)
Temporomandibular joint dysfunction (TMD) is characterized by the presence of signs and symptoms that lead to functional changes in this joint. Most of the times with a multifactorial etiology, it can be associated to systemic diseases, such as rheumatoid arthritis (RA).  Objectives: to evaluate the prevalence of TMD in a cohort of women with RA, as well as possible links between its presence and disease activity and duration, smoking and frequent consumption of chewing gum, compared with a control group of healthy controls. Material and methods: Fonseca's Anamnesic Questionnaire, validated for the assessment of TMD, was applied to a cohort of 63 female outpatients with a diagnosis of RA according to the American College of Rheumatology classification. To obtain patient's clinical information, we reviewed the hospital medical records. Data were introduced on the SPSS 17.0 system and ANOVA and e Kruskall-Walis tests and Tukey analysis were performed, as well as chi-square test. Results: It was found that the prevalence of TMD in the cohort of women with RA was similar to those in the control group. There was also no correlation between the regular consumption of chewing gum and smoking habits and TMD in RA patients. The duration of RA was also not correlated with a higher prevalence of TMD in this study. Conclusion: the results obtained in our study seem to reflect the multifactorial etiology of TMD, where RA is only one of the multiple possible causes and, secondly, the high sensitivity and low specificity of the index used, which would explain the high number of TMD cases found in the control group.